2014
DOI: 10.1007/s00787-014-0523-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of SSRIs among Danish children: a nationwide study

Abstract: Our objective was to describe the use of selective serotonin reuptake inhibitors (SSRIs) in the entire Danish population of children and adolescents from 1995 to 2011. Data on filled SSRIs were obtained for all children in Denmark aged 5-17 during 1995-2011. The amount and type of SSRIs filled were calculated as well as incidence rates and prevalence proportions. Furthermore, we looked at concurrent use of other psychotropic drug treatment duration. A total of 23,547 children aged 5-17 used SSRIs during the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…Only a weak increase was observed in boys. This is in line with previous studies that have separately studied either diagnosed or self‐reported depression or prescription of ADs .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Only a weak increase was observed in boys. This is in line with previous studies that have separately studied either diagnosed or self‐reported depression or prescription of ADs .…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have shown an increasing use of antidepressants (ADs) among adolescents in European countries and in the USA . In Norway, we have also seen a pronounced increase in the use of ADs between 2009 and 2016, particularly among 16‐ to 17‐year‐old girls .…”
Section: Introductionmentioning
confidence: 98%
“…Treatment guidelines for pediatric depression, OCD, and anxiety disorders emphasize that drug‐therapy should always be given in combination with psychosocial interventions and non‐pharmacological treatment, and with a close monitoring of beneficial and harmful effects . In recent years, a trend of increasing use of ADs among children and adolescents has been observed in the USA, Canada, and European countries . However, large differences in prescribing prevalence of AD drugs exist between countries, with the highest use of ADs in the USA .…”
Section: Introductionmentioning
confidence: 99%
“…Such a trend was also found in countries like the UK [13], but only to a slight extent or not at all in other countries, such as Canada [27] or Denmark [28]. The decrease in antidepressant initiation in young people was likely related to media coverage of the potential for treatment-emergent suicidality with antidepressant treatment [15], but this effect appears to have been transient.…”
Section: Discussionmentioning
confidence: 98%